2021
DOI: 10.1186/s40104-021-00600-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary oregano essential oil supplementation improves intestinal functions and alters gut microbiota in late-phase laying hens

Abstract: Background Dietary essential oil (EO) supplementation can exert favorable effects on gut health in broilers. However, it is unknown whether EO could improve intestinal functions, consequently beneficial for egg performance and quality in late-phase laying hens. This study was aimed to investigate the potential effects of EO on production performance, egg quality, intestinal health and ileal microbiota of hens in the late phase of production. A total of 288 60-week-old Hy-line Brown laying hens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 69 publications
4
51
2
Order By: Relevance
“…It has been reported that dietary essential oils could significantly increase the eggshell thickness [20,29]. In our study, the eggshell thickness of EO1 and EO2 was lower (P < 0.05) than that of control and AGP at week 4, but the difference disappeared at week 8, which may be due to altered flora structure [30].…”
Section: Discussioncontrasting
confidence: 42%
“…It has been reported that dietary essential oils could significantly increase the eggshell thickness [20,29]. In our study, the eggshell thickness of EO1 and EO2 was lower (P < 0.05) than that of control and AGP at week 4, but the difference disappeared at week 8, which may be due to altered flora structure [30].…”
Section: Discussioncontrasting
confidence: 42%
“…Alloprevotella is known as an opportunistic pathogen; however, previous studies have noted that the increased abundance of Alloprevotella genera was linked to better intestinal health [ 50 ]. Besides this, the genus Romboutsia is a valuable intestinal biomarker maintaining host health, and Enterococcus with natural antimicrobial probiotic properties could prevent diarrhea in animal production [ 51 ]. However, their roles in gut health and functions of birds need to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…This increase could be considered beneficial as Clostridia are not only dominant in ceca [ 126 ], but they also contribute to the maintenance of overall gut function, especially through butyrate production [ 127 ]. Deinococcus , Bacillaceae and Caulobacteriales were increased in ileal digesta of laying hens fed on a dietary supplementation of EOs, promoting an increase of digestive enzyme activity leading to improved feed utilization efficiency [ 128 ]. Moreover, although some authors reported a decrease of the relative abundance of beneficial commensal bacteria such as Lactobacillus by plant extract supplementation [ 43 , 129 ], several others found Clostridiales and/or Lactobacillales to be higher in broilers supplemented with EOs of carvacrol and thymol [ 130 , 131 ] or thymol, eugenol and piperine [ 121 ].…”
Section: Effects Of Phytogenic Feed Additives On Chickensmentioning
confidence: 99%